Examining Driving and Participation 5 Years After Traumatic Brain Injury. (July 2018) - Erler, Kimberly S.; Juengst, Shannon B.; Smith, Diane L.; O'Neil-Pirozzi, Therese M.; Novack, Thomas A.; Bogner, Jennifer A.; Kaminski, Jamie; Giacino, Joseph T.; Whiteneck, Gale G.
Participation is often considered a primary goal of traumatic brain injury (TBI) rehabilitation, but little is known about the influence of driving on participation after TBI. The objective of this study was to examine the independent contribution of driving status to participation at 5 years post TBI, after controlling for demographic, psychosocial, and functional factors. Participants ( N = 2, 456) were community-dwelling individuals with moderate to severe TBI, age 18 to 65 at time of injury, and enrolled in the TBI Model Systems (TBIMS) National Database (NDB). Hierarchical linear regressions for the dependent variable of participation at 5 years post TBI were performed. Findings showed that driving was a highly significant independent predictor of participation and was a stronger relative predictor of participation than FIM® Cognitive, FIM® Motor, and depression. The independent contribution of driving to participation suggests the need to develop evidenced-based occupational therapy assessments and interventions that facilitate safe engagement in the occupation of driving to address the long-term goal of improved participation.